2021
DOI: 10.3390/ma14092202
|View full text |Cite
|
Sign up to set email alerts
|

Methodology for the Quality Control Process of Additive Manufacturing Products Made of Polymer Materials

Abstract: The objective of this publication is to present a quality control methodology for additive manufacturing products made of polymer materials, where the methodology varies depending on the intended use. The models presented in this paper are divided into those that are manufactured for the purpose of visual presentation and those that directly serve the needs of the manufacturing process. The authors also a propose a comprehensive control system for the additive manufacturing process to meet the needs of Industr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 29 publications
0
33
0
Order By: Relevance
“…Rapid prototyping is a promising method that can support the efficient production of models and prototypes [ 1 , 2 , 3 ]. Additive manufacturing (AM) technologies allow components with adjustable geometry and mechanical properties [ 4 , 5 , 6 ] that can be used in a wide variety of industry sectors to be obtained [ 7 ]. Fused deposition modelling (FDM), also known as fused filament fabrication (FFF), is an AM process based on extrusion, where material as a filament is melted and selectively dispensed through a fine nozzle layer upon layer according to the slice model [ 8 , 9 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Rapid prototyping is a promising method that can support the efficient production of models and prototypes [ 1 , 2 , 3 ]. Additive manufacturing (AM) technologies allow components with adjustable geometry and mechanical properties [ 4 , 5 , 6 ] that can be used in a wide variety of industry sectors to be obtained [ 7 ]. Fused deposition modelling (FDM), also known as fused filament fabrication (FFF), is an AM process based on extrusion, where material as a filament is melted and selectively dispensed through a fine nozzle layer upon layer according to the slice model [ 8 , 9 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The quality and mechanical properties of FDM parts can be improved if modifications before, on site and after manufacturing are made. In order to improve the quality, some works have developed a control system for the most common additive manufacturing processes and materials, including dimensional parts control [ 14 ]. Other studies improve the properties evaluating the effect of infill parameters [ 15 , 16 ], such as layer thickness, raster direction and layup order.…”
Section: Introductionmentioning
confidence: 99%
“…Budzik et al compared car mirror holder parts manufactured by MJ, FDM and DLP in terms of visual control, application of a caliper and application of a contactless optical system. They stated that the MJ method was the most precise technique [ 97 ]. Wesemann et al compared the accuracy of occlusal splints produced by SLA, DLP and MJ and concluded that SLA showed the smallest manufacturing deviations [ 98 ].…”
Section: Process and Materialsmentioning
confidence: 99%